Chemoimmunotherapy in Advanced, PD-1 Refractory Cutaneous Squamous Cell Carcinoma: Insights From Two Immunocompromised Patient Cases - Golbarg Rahimi; Gino K. In (Case Reports in Oncological Medicine)
Cutaneous squamous cell carcinoma (cSCC) is one of the most prevalent malignancies worldwide, and a subset of patients, particularly immunocompromised individuals, will face heightened risks of metastasis and mortality. This report examines two cases of immunocompromised patients treated with a combination of platinum- and taxane-based chemotherapy together with PD-1 inhibition, having progressed after PD-1 monotherapy. The first patient, a 54-year-old man with HIV and recurrent metastatic cSCC, had rapid progression of disease while undergoing PD-1 inhibition with cemiplimab but later achieved tumor control when treated with pembrolizumab, carboplatin, and paclitaxel. The second patient, a 36-year-old man with cystic fibrosis and a history of lung transplantation, had no signs of response to cemiplimab but experienced a partial response when treated with cemiplimab, carboplatin, and paclitaxel. These cases suggest that combining chemotherapy with PD-1 inhibition may help overcome primary resistance to PD-1 therapy in advanced cSCC.